Pocket parks as community building blocks: A focus on Stapleton, CO. Issue 5 (19th October 2016) - Gibson, Huston; Canfield, Jessica
Abstract: Concern for resources and energy, as well as limited physical space, has created a market for communities that use compact development with small residential lots to achieve efficient design. The Stapleton development in Denver, Colorado, is a smart growth, new urban-style community that offers shared neighborhood pocket parks to residents instead of large individual yards for outdoor activities. Our study assesses resident perceptions of pocket parks as an alternative to private yards and investigates pocket parks as places that foster community interaction. This article is informed by two empirical studies: a park preference survey and a series of walking interviews held with community members. We found that, in Stapleton, pocket parks do help foster community interaction and are generally perceived as a positive community amenity. Our study contributes to the discourse on social interaction in communal spaces, particularly in smart growth, new urban-style developments where pocket parks are offered in lieu of large residential yards.